Studies on Schismatoglottideae (Araceae) of Borneo LXIII: Three New Species for the Schismatoglottis Patentinervia Clade - BOYCE, PETER C. (Borneo Journal of Resource Science and Technology, 2017)
Three new species of the Schismatoglottis Patentinervia Clade are described and illustrated from Sarawak, Malaysian Borneo, and included in an updated identification key to the described species in clade. Two of the novelties are from Serian Division, SW Sarawak: Schismatoglottis pichinensis P.C. Boyce sp. nov., restricted to forested limestone at low altitudes, and S. puncakborneensis P.C. Boyce sp. nov., occurring in moist upper hill forest on Paleogene sandstones. The third, S. gephyra P.C. Boyce sp. nov., is a lowland species from NE Borneo on Oligocene sedimentaries. Recognition of these three species takes the Patentinervia Clade to nine described species, of which seven have only been formally recognized since 2000. Keywords: Borneo, Sarawak, aroids, taxonomy